Chemical modifications of Tonda Gentile Trilobata hazelnut and derived processing products under different infrared and hot‐air roasting conditions: a combined analytical study. (15th April 2018) - Binello, Arianna; Giorgis, Marta; Cena, Clara; Cravotto, Giancarlo; Rotolo, Laura; Oliveri, Paolo; Malegori, Cristina; Cavallero, Maria Chiara; Buso, Stefania; Casale, Monica
Abstract: BACKGROUND: For the processing industry, it is crucial to know what effect the roasting process and conditions have on hazelnut quality. The present study investigates, for the first time, the effects of hot‐air and infrared (IR) roasting at different time–temperature combinations on Tonda Gentile Trilobata hazelnut: whole kernels and derived processing products (paste and oil). RESULTS: The nutritional and physical characteristics of hazelnuts and processing products were investigated to determine the influence of the different roasting conditions as a function of intended use. The antioxidant profile (2.2‐diphenyl‐1‐picrylhydrazyl radical, oxygen radical absorbance capacity and total phenolic content) were analyzed on roasted hazelnut and paste extracts. For a comprehensive understanding of the complex biochemical phenomena occurring during roasting, E‐nose and near‐IR spectroscopy were also applied. All analytical data were processed using univariate and multivariate data analyses. Hazelnuts derived from IR roasting at higher temperatures (195 °C) showed a richer antioxidant profile and a more intense flavour. On the other hand, the yield associated with the oil extraction under the same conditions was unsatisfactory, making this process completely inadequate for oil production. Oil obtained by hot‐air roasting and IR roasting at lower temperature (135 °C) was found to be of good quality, showing rather similar acidity grade, peroxide number and acidic composition. In particular, a slightly but significantly lower acidity was related to lower roasting temperatures (0.21–0.22% versus 0.27% for higher temperatures). All roasting conditions tested allowed the quantitative homogeneous hazelnut paste to be obtained and, from a rheological point of view, a higher roasting temperatures resulted in pastes characterized by higher density and viscosity values. CONCLUSION: The use of IR was found to be a promising alternative method for hazelnut roasting, as a result of its capability with respect to preserving nutritional values and enhancing organoleptic quality. © 2018 Society of Chemical Industry